Penggunaan Alat Peraga untuk Meningkatkan Motivasi dan Hasil Belajar Matematika Peserta Didik Kelas VI SD Inpres Lisabheto: - Anvrina Iry, Dominika; Wahyuningsih, Wahyuningsih; Rahmawati, Tanti Diyah (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2022)
The method used in this study is Classroom Action Research (CAR) using teaching aids to find out whether there is an increase in learning outcomes and the motivation of students in class VI SD Inpres Lisabheto in mathematics, especially material building. Based on the pre -survey results, explaining that many student learning outcomes in pre -cycles have not yet reached the KKM, as well as the low motivation to learn students. This can be seen at the first meeting with an average learning outcome of 65.85 completeness level of 50% and the second meeting averaged 75.78 disjolized 1 so that the completeness level of 68.75%. Because there are learning outcomes that have not yet reached the KKM, they will be continued. On average in the second cycle the first meeting was 90.01 completeness level of 100% and at the second meeting an average of 95.63 with a completeness level of 100%. In this second cycle it has reached KKM with a value of ? 66. While the motivation of student learning in the first cycle with an average of 49.9 and the second cycle reaches 62.8. Based on the average learning motivation in cycle 1 and cycle 2 it can be concluded that the media of teaching aids can affect student motivation so that it provides maximum learning outcomes after evaluating class VI at SD Inpres Lisabheto Academic Year 2021/2022